1993
DOI: 10.1007/bf03188793
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, tissue distribution and excretion of radiolabelled compounds in rats after administration of [14C]-l-α-glycerylphosphorylcholine

Abstract: The kinetics and metabolism of L-alpha-glycerylphosphoryl-choline (alpha-GPC) were investigated in male and female rats after i.v. (10 mg/kg) and oral doses (100-300 mg/kg). alpha-GPC was labelled with [14C]-glycerol ([14G]-GPC) or [14C]-choline ([14C]-GPC). Different kinetic and metabolic profiles were observed after i.v. and oral administration. It is assumed that alpha-GPC is hydrolyzed by phosphodiesterases in the gut mucosa. The different labelled metabolites have different kinetic properties of absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…choline precursors and is incorporated into brain phospholipids within 24 h from absorption [35]. Preclinical studies, have documented that choline alphoscerate increases the release of acetylcholine in rat hippocampus, facilitates learning and memory, counters cognitive deficit in experimental models of aging brain and reverses memory deficits induced by scopolamine administration (see [23]).…”
Section: Choline Alphosceratementioning
confidence: 98%
“…choline precursors and is incorporated into brain phospholipids within 24 h from absorption [35]. Preclinical studies, have documented that choline alphoscerate increases the release of acetylcholine in rat hippocampus, facilitates learning and memory, counters cognitive deficit in experimental models of aging brain and reverses memory deficits induced by scopolamine administration (see [23]).…”
Section: Choline Alphosceratementioning
confidence: 98%
“…The molecular mechanisms underlying CDP-choline-induced cognitive enhancement are still unclear, but one possibility is that CDP-choline counters the progression of ischemic damage by reducing the release of free fatty acids [44] . Choline alphoscerate, a semi-synthetic derivative of lecithin that does not carry the electrical charge of endogenous choline, can be incorporated into brain phospholipids within 24 h of absorption, resulting in a more rapid increase in free plasma choline than other uncharged choline precursors [54] . Preclinical studies have demonstrated that choline alphoscerate increases the release of ACh in the rat hippocampus and facilitates learning and memory in animal models of aging [55] .…”
Section: Cholinergic Precursorsmentioning
confidence: 99%
“…Both are natural, water-soluble compounds providing comparable effects in different conditions [11]. After oral administration, both CDP-choline and choline alphoscerate have been shown to cross the blood-brain barrier and reach the central nervous system, where they are incorporated into the phospholipid fraction of the neuronal plasma membrane and in microsomes [12,13].…”
Section: Introductionmentioning
confidence: 99%